28б5. Документы и материалы по истории советско-польских отношений. – М.: Наука. 1983. – Т.11. – Янв. 1956. г. – Дек. 1960. – 603 с. - АКТОНЮК , С.М.; ЮРЧЕНКО , О.А. (Український історичний журнал, 1984)
.